PENERAPAN PEMBELAJARAN BERDIFERENSIASI MENURUT KURIKULUM MERDEKA UNTUK MENGEMBANGKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DENGAN TOPIK STATISTIKA [IMPLEMENTATION OF DIFFERENTIATED LEARNING ACCORDING TO THE MERDEKA CURRICULUM TO DEVELOP STUDENTS' LEARNING MOTIVATION IN MATHEMATICS LEARNING ON THE TOPIC OF STATISTICS] - Iswandi, Nivea; Dirgantoro, Kurnia Putri Sepdikasari (Universitas Pelita Harapan, 2024)
Learning motivation is important to encourage students to do learning activities. With good learning motivation, students will be able to face learning challenges and successfully achieve learning goals. However, the fact is that 24 students of class XII in one of the schools in Tangerang have low learning motivation. One of the reasons is because the learning method used does not provide space for students to learn according to their diverse characteristics. To overcome this problem, the author applied differentiated learning. Students are unique images of God. They are given different talents by God so they need to be served according to their needs in order to develop and use their talents for the glory of God. The purpose of this study is to examine the implementation of differentiated learning according to the Merdeka Curriculum to develop student learning motivation in mathematics learning on the topic of statistics. The research method used is descriptive qualitative. The results showed that the implementation of differentiated learning according to the Merdeka Curriculum can develop student learning motivation by fulfilling the four indicators of learning motivation through the stages of mapping student needs, planning differentiated learning, implementing differentiated learning, and evaluation and reflection.BAHASA INDONESIA ABSTRACT: Motivasi belajar penting untuk mendorong siswa melakukan kegiatan belajar. Dengan motivasi belajar yang baik, siswa akan mampu menghadapi tantangan pembelajaran dan berhasil mencapai tujuan pembelajaran. Namun, faktanya 24 siswa kelas XII di salah satu sekolah di Tangerang memiliki motivasi belajar yang rendah. Salah satu penyebabnya karena metode pembelajaran yang digunakan tidak memberi ruang kepada siswa untuk belajar sesuai dengan karakteristiknya yang beragam. Untuk mengatasi masalah tersebut, peneliti menerapkan pembelajaran berdiferensiasi. Siswa merupakan gambar Allah yang unik. Mereka diberi talenta yang berbeda-beda oleh Allah sehingga siswa perlu dilayani sesuai kebutuhannya supaya dapat mengembangkan dan menggunakan talentanya untuk kemuliaan Allah. Tujuan penelitian ini adalah menjelaskan penerapan pembelajaran berdiferensiasi menurut Kurikulum Merdeka untuk mengembangkan motivasi belajar siswa pada pembelajaran matematika dengan topik statistika. Metode penelitian yang digunakan adalah kualitatif deskriptif. Hasil penelitian menunjukkan bahwa penerapan pembelajaran berdiferensiasi menurut Kurikulum Merdeka dapat mengembangkan motivasi belajar siswa dengan terpenuhinya keempat indikator motivasi belajar melalui tahap memetakan kebutuhan siswa, merencanakan pembelajaran berdiferensiasi, melaksanakan pembelajaran berdiferensiasi, serta evaluasi dan refleksi.